2017
DOI: 10.1055/s-0043-103280
|View full text |Cite
|
Sign up to set email alerts
|

MRI Sequences in Head & Neck Radiology – State of the Art

Abstract: ZUSAMMENFASSUNGHintergrund Magnetic resonance imaging (MRI) ist ein essentielles bildgebendes Verfahren für die Beurteilung von Kopf-Hals Erkrankungen. Die diagnostische Aussagekraft der MRI ist jedoch stark von der entsprechenden Auswahl und Interpretation der Protokolle und Sequenzen abhängig. Das Ziel dieses Beitrags ist es, State-of-the-art-Sequenzen für die klinische Routine der Kopf-Hals-MRI zusammenzufassen und die Evidenz zu beschreiben, für welche medizinische Fragestellungen diese Sequenzen nützlich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 63 publications
0
48
0
2
Order By: Relevance
“…FIESTA provides a high signal in tissues with high T2/T1 ratios, such as cerebrospinal fluid and fat, enables submillimeter spatial resolution, and has been mainly used to evaluate the cerebellopontine angles and inner ear, allowing the precise differentiation between branches of the cranial nerves. [ 8 ] Recently, this sequence has been reported to be useful in the demonstration of not only intraventricular lesions but also parenchymal lesions. [ 4 5 ] In the present study, FIESTA showed intralesional reticulate or broad-line structures in inflammatory demyelinating lesions in the DGM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIESTA provides a high signal in tissues with high T2/T1 ratios, such as cerebrospinal fluid and fat, enables submillimeter spatial resolution, and has been mainly used to evaluate the cerebellopontine angles and inner ear, allowing the precise differentiation between branches of the cranial nerves. [ 8 ] Recently, this sequence has been reported to be useful in the demonstration of not only intraventricular lesions but also parenchymal lesions. [ 4 5 ] In the present study, FIESTA showed intralesional reticulate or broad-line structures in inflammatory demyelinating lesions in the DGM.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] A new MRI technique, fast imaging employing steady-state acquisition (FIESTA) MRI, is suitable for depicting the cranial nerves in the cisterns because the sequence has a high spatial resolution and signal-to-noise ratio. [ 1 8 ] FIESTA is also useful for the demonstration and identification of parenchymal solitary cysticercus granuloma, suggesting that FIESTA can demonstrate small structures or lesions in not only the cisterns but also the brain. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…MRI is extremely useful in assessment of neck lesions due to its excellent soft tissue delineation and multiplaner imaging capabilities but is limited by its unsuitability in claustrophobic patients, and individuals with certain devices like pacemakers and cochlear implants. Moreover its availability is not uniform and cost is also prohibitive [8,9,10] .…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-weighted MRI sequences can identify change in cytoarchitecture and cell density, allowing the use of apparent diffusion coefficient (ADC) values for the characterization of small (4-9 mm) metastatic lymph nodes ( 3 ) , for which the morphology and size criteria would yield false-negative results ( 4 ) . In addition, many studies have demonstrated the importance of post-treatment assessment with diffusion-weighted imaging, suggesting that, by as soon as two weeks after the initiation of treatment, ADC values can indicate whether or not the prescribed pharmacological treatment has been successful ( 5 ) .…”
mentioning
confidence: 99%
“…The various techniques of dynamic study after injection of contrast medium allow characterization of vascular permeability and identification of neovascularization, suggestive of metastatic lymph nodes ( 6 ) . Spectroscopy demonstrates a change in the concentration of metabolites, which can guide the diagnosis ( 3 ) .…”
mentioning
confidence: 99%